2020
DOI: 10.1530/eje-19-0809
|View full text |Cite
|
Sign up to set email alerts
|

Random ‘spot’ urinary metanephrines compared with 24-h-urinary and plasma results in phaeochromocytomas and paragangliomas

Abstract: Background In patients with phaeochromocytomas or paragangliomas (PPGLs), 24-h urine collections for metanephrines (uMNs) are cumbersome. Objective To evaluate the diagnostic utility of ratios to creatinine of ‘spot’ uMNs. Methods Concentrations of uMNs and plasma metanephrines (pMNs) were measured by HPLC-mass-spectrometry. We retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The survey also found that 10 laboratories accept either overnight or random urine samples for UMET, at least in certain circumstances. The Endocrine Society Guideline states that a 24-h urine collection is preferred, although there is a some evidence that overnight or random UMET may perform well as a diagnostic test compared to 24-h collection [41][42][43] While all centres using PMET requested EDTA plasma, the acceptance criteria were quite variable with the maximum permissible delay between sample collection and centrifugation varying between 15 min and 6 h. Having a defined policy in place for the acceptance of PMET samples is important as published data show that while PMET may be stable pre-centrifugation for up to 3 h when kept at 4°C, 44 concentrations change quite rapidly at room temperature with concentrations potentially initially increasing (due to residual activity of the enzyme catechol-O-methyltransferase) and then undergoing degradation. 44,45 Post-centrifugation, metanephrines are not stable at room temperature with significant degradation observed within 24 h. Plasma kept at 4°C appears to be stable for up to 3 days without significant degradation and frozen plasma is stable for at least 1 month.…”
Section: Sample Requirementsmentioning
confidence: 99%
“…The survey also found that 10 laboratories accept either overnight or random urine samples for UMET, at least in certain circumstances. The Endocrine Society Guideline states that a 24-h urine collection is preferred, although there is a some evidence that overnight or random UMET may perform well as a diagnostic test compared to 24-h collection [41][42][43] While all centres using PMET requested EDTA plasma, the acceptance criteria were quite variable with the maximum permissible delay between sample collection and centrifugation varying between 15 min and 6 h. Having a defined policy in place for the acceptance of PMET samples is important as published data show that while PMET may be stable pre-centrifugation for up to 3 h when kept at 4°C, 44 concentrations change quite rapidly at room temperature with concentrations potentially initially increasing (due to residual activity of the enzyme catechol-O-methyltransferase) and then undergoing degradation. 44,45 Post-centrifugation, metanephrines are not stable at room temperature with significant degradation observed within 24 h. Plasma kept at 4°C appears to be stable for up to 3 days without significant degradation and frozen plasma is stable for at least 1 month.…”
Section: Sample Requirementsmentioning
confidence: 99%
“…The electrochemical characterization of the microneedle electrode before and after h-nPG electrodeposition has already been investigated by CV in a solution of Fe(CN) 6 3− / 4− , as reported in our previous work [36]. It is interesting to note that the enhancement of both anodic and cathodic peak current densities after the h-nPG electrodeposition was much larger than that registered with planar gold electrodes after the same modification.…”
Section: Characterizationmentioning
confidence: 78%
“…EIS experiments were carried out at equilibrium potential called open-circuit potential (OCP) without potential of the redox probe (0.22 V vs Ag/AgCl), bias voltage in the frequency range of 0.1-10 3 Hz using an AC signal of 10-mV amplitude at a formal potential of the redox probe (0.22 V vs Ag/AgCl), using Autolab Potentiostat/Galvanostat (Eco Chemie, Netherlands). EIS measurements were performed using 10 mL of PBS solution containing mixture of 5 mM Fe(CN) 6 3− /Fe(CN) 6 4− , as electrochemical probe.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging studies have noted that the sensitivity and specifi city of spot urine samples correlate well with those of 24-hour samples, but at present the evidence is insuffi cient to recommend adopting this strategy in routine clinical practice. 2,11 Vanillylmandelic acid has poor sensitivity and is not indicated in the initial biochemical workup for possible PPGLs. 12…”
Section: ■ Initial Biochemical Testing: Focus On Sensitivitymentioning
confidence: 99%